2020
DOI: 10.1097/shk.0000000000001349
|View full text |Cite
|
Sign up to set email alerts
|

Acute Inflammation in Traumatic Brain Injury and Polytrauma Patients Using Network Analysis

Abstract: Introduction: Traumatic brain injury (TBI) is associated with secondary injury to the central nervous system (CNS) via inflammatory mechanisms. The combination of polytrauma and TBI further exacerbates the inflammatory response to injury; however, combined injury phenomena have not been thoroughly studied. In this study, we examined the inflammatory differences between patients with TBI versus patients with polytrauma, but no TBI (polytrauma). We hypothesize that patients with TBI have a heightened… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
8
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 48 publications
4
8
1
1
Order By: Relevance
“…Thus, we assayed CCL2 in this study. TBI and intracerebral hemorrhage patients show elevated plasma and serum levels of CCl2 as early as 2 h onwards and show poor outcomes [59,60]. Our present study has shown increased CCL2 levels in the brain and the serum of weight drop-induced TBI mice.…”
Section: Mediators Of Inflammationsupporting
confidence: 59%
“…Thus, we assayed CCL2 in this study. TBI and intracerebral hemorrhage patients show elevated plasma and serum levels of CCl2 as early as 2 h onwards and show poor outcomes [59,60]. Our present study has shown increased CCL2 levels in the brain and the serum of weight drop-induced TBI mice.…”
Section: Mediators Of Inflammationsupporting
confidence: 59%
“…IL-6, TNF and fractalkine were elevated in blood up to 6 months following injury [ 57 ]. TBI and polytrauma patients exhibit clinically relevant cytokine patterns in blood [ 58 60 ], CSF and brain-ECF [ 22 ], which was similar to what we noticed in our cohort, and demonstrates cytokine release from brain and other injured tissues.…”
Section: Discussionsupporting
confidence: 82%
“…IL-6, TNF and fractalkine were elevated in blood up to 6 months following injury [69]. TBI and polytrauma patients exhibit clinically relevant cytokine patterns in blood [70][71][72], CSF and brain-ECF [36], which was similar to what we noticed in our cohort, and speaks for a pronounced cytokine release from brain and other injured tissues. Altogether, we saw a relatively strong association between cytokines and age, sex as well as injury severity markers.…”
Section: Patient Demographics Affect Cytokine Levelssupporting
confidence: 87%